Vedic Science and Modern Science - King, Anna S. (Journal for the academic study of religion, 2012)
This article raises questions about how non-Christian theologies, especially literalist or ‘fundamentalist’ types, respond to, and join in, the debate over modern science and religion. It focuses attention on the response of Indian religious traditions to one particular theme in the Western discourse on modernity and religion; namely, the notion of rational science as seemingly opposed to irrational religions, and ef?cacious technology as seemingly opposed to ineffective rituals. It presents the case study of ISKCON, a branch of Gaudiya Vaishnavism, which makes use of these oppositions by classifying its own teachings as scienti?c, and by asserting that science and religion are ultimately reconcilable because true scienti?c knowledge can only come from religion. This strategy sustains its position as a universalist religion within a modern environment that appears to be hostile towards religion. This article explores why ISKCON in its public documents adopts largely confrontational attitudes to science and historical and archaeological scholarship, and why, while some of these texts claim to lay out the evidence fully and fairly, they are in general characterised by religious apologetic rather than reason and argument. It examines Prabhupada’s ‘scienti?c legacy’ in the form of ISKCON’s public and semi-of?cial pronouncements on history, culture and science, and considers the notion that any ethical or theological principle must be consistent with the natural world as we experience it. Methodologically this article goes beyond what might be seen as the natural boundaries of religious studies by engaging vigorously with ISKCON’s public stance towards science. It might therefore seem that the author attempts to be theologically normative. However, the aim is not to press a particular (liberal) theological approach, but to clarify ISKCON’s position and to offer a critique. The article argues that ISKCON often con?ates science with scientism and that its representation of ‘Western science’ is ideologically motivated. ISKCON compares the restrictive and reductive effects of modern scienti?c paradigms with the harmony brought about by revealed Vedic science. However, this article asks whether ISKCON’s own literalist understanding of Vedic literature and culture is compatible with a positive evaluation of modern scienti?c achievements. The twenty-?rst century may need scienti?c solutions to a whole range of issues, from global warming to food security, and from ?ghting crime to developing new medicines. While ISKCON seeks to resacralise the world, it may do so at the cognitive cost of demoting reason and modern science.